ANALYSIS OF URINARY INCONTINENCE IN WOMEN - Satibaldiyeva Zebo Shuxratullayevna; Fayazov Fazliddin Fayazjanovich (European Science Publishing, 2025)
In this presentation, the problem of urinary incontinence in women in Andijan region and Fergana region is analyzed. In the process of analysis, attention was paid to the causes, mechanisms, methods of treatment and statistical data. The problem also includes the opinion of society and recommendations. The main types of urinary incontinence, their diagnosis and treatment methods are covered in detail in the study. the social consequences are also studied. The importance of preventive measures, conservative and surgical interventions is emphasized in the solution of the problem.
Keywords: Urinary incontinence in women, types of urinary incontinence, urinary tract infection, menopause, urinary incontinence, treatment methods for urinary incontinence, urinary system hygiene for women.